The German-Turkish relations during the Macedonian reforms (1903-1908) - Gao Jianzhi («Քոփի Փրինթ» տպագրատուն)
In February 1903, with the introduction of Austro-Russian “The Vienna Scheme”, the Macedonian issue became a European-wide problem. The diplomatic games of the Great Powers over the Macedonian reforms became one of the key factors affecting the adjustment of relations among the Great Powers. In order to expand its influence in Turkey and develop German-Turkish relations, Germany mostly stayed out of the Concert of Europe on Macedonian reforms and hindered the reform process. However, when faced with a choice between Austria-Hungary and the Ottoman Empire, Germany sided with its ally Austria- Hungary. The Ottoman Empire took advantage of the differences among the Great Powers on the Macedonian reforms to slow down the reform process as much as possible and maintain the integrity of its European territory. However, in the face of the coercive power of the Great Powers, the Ottoman Empire’s claims of sovereignty and struggles often faced failures. In order to avoid the complete collapse of the Empire, the Ottoman Empire tried to develop German-Turkish friendship during the Macedonian reforms, and this diplomatic choice became the main basis for the implementation of national policy in the future and promoted the reorganization of the European power structure. 1903 թվականի փետրվարին ավստրո-ռուսական «Վիեննայի համակարգի» ներդրմամբ մակեդոնական հարցը վերածվեց համաեվրոպական խնդրի։ Մեծ տերությունների դիվանագիտական ջանքերը Մակեդոնիայի բարեփոխումների շուրջ դարձան այն կարևոր գործոններից մեկը, որն ազդեց մեծ տերությունների միջև հարաբերությունների կարգավորման վրա։ Փորձելով ընդլայնել իր ազդեցությունը Թուրքիայում և զարգացնել գերմանա-թուրքական հարաբերությունները Մակեդոնիայի բարեփոխումների հետ կապված` Գերմանիան մնաց եվրոպական համակարգի լուսանցքում և խոչընդոտեց բարեփոխումների գործընթացին: Այնուամենայնիվ, Գերմանիան, կանգնելով Ավստրո-Հունգարիայի և Օսմանյան կայսրության միջև ընտրության առջև, անցավ իր դաշնակից Ավստրո-Հունգարիայի կողմը: Օսմանյան կայսրությունը, օգտվելով մակեդոնական բարեփոխումների հարցում մեծ տերությունների միջև առկա տարաձայնություններից, փորձեց հնարավորինս դանդաղեցնել բարեփոխումների գործընթացը և պահպանել իր եվրոպական տարածքի ամբողջականությունը։ Կայսրության լիակատար փլուզումից խուսափելու համար Օսմանյան կայսրությունը փորձեց մակեդոնական բարեփոխումների ընթացում զարգացնել գերմանա-թուրքական բարեկամությունը, և ապագայում դիվանագիտական այս ընտրությունը դարձավ պետական քաղաքականության իրականացման հիմքը:
Keywords: German-Turkish Relations